Mechanical Characterization of Different Aluminium Foams at High Strain Rates - Amaro, Ana M. (Materials (Basel), 2019)
Samples having nominal compositions of AlSi12 and Al6082-T4 were prepared using a lost wax casting process, with nominal relative densities of 20%, 40%, and 60%, as well as arrangements of a uniform cell structure (US) or a dual-size cell (DS). For comparison, samples of aluminium foam-filled tubes having the same nominal composition were also prepared with the same technique, with nominal relative densities of 20% and similar arrangements (US and DS). Impact tests at different velocities were performed using a split Hopkinson pressure bar (SHPB). It is possible to conclude that Al6082-T4 foams have better performance, in both configurations, than the AlSi12 ones. Considering a uniform cell structure and a density of 20%, the absorbed energy by the Al6082-T4 foams was around 25% higher than the value observed for the AlSi12 ones. In terms of arrangement, the US structure presents absorbed energy around 57% lower than the DS ones, while the AlSi12 foams with a relative density of 20% were compared. Finally, the absorbed energy growths from 2.8 × 10(5) to 5.2 × 10(5) J/m(3), when the density increased from 20% to 60%. However, when these foams were involved with a tube, the performances increased substantially.